Which ear should we choose for cochlear implantation in the elderly: The poorer or the better? Audiometric outcomes, quality of sound, and quality-of-life results. (2nd December 2015) - Lassaletta, Luis; Calvino, Miryam; Sánchez-Cuadrado, Isabel; Pérez-Mora, Rosa M.; Gavilán, Javier
Abstract: Conclusions: Cochlear implantation in the poorer ear of an elderly patient does not predict poorer post-operative audiological, quality-of-life (QoL), and quality of sound results. Objectives: To determine whether choosing the 'better' or the 'poorer' ear for cochlear implantation impacts performance outcome in an elderly population. Methods: Forty-two out of 73 elderly (≥ 60 years) cochlear implant users with some residual hearing in at least one ear were selected. Three criteria were used to group the patients as 'better' or 'poorer' ear implanted; (C1) based on previous use of hearing aid, (C2) pre-operative PTA, and (C3) pre-operative speech discrimination. The Glasgow Benefit Inventory (GBI) and the Hearing Implant Sound Quality Index (HISQUI) were used to measure QoL and quality of sound, respectively. Results: The mean post-operative PTA was 38.7 ± 7.2 dBHL. In quiet, the mean disyllabic SDS at 65dBSPL was 75.4 ± 18.5, whereas the discrimination of sentences was 95.0% ± 6.9. The mean total GBI score was 30.9 ± 21.8, 92.9% of patients reporting a positive score. The mean HISQUI score was 111.3 ± 36.0, which corresponds to 'moderate' sound quality. No significant differences were found between both groups in terms of audiological outcomes, HISQUI scores or GBI scores when considering each of the three criteria.